APLIKASI SISTEM PAKAR DIAGNOSA PENYAKIT GASTROENTERITIS BERBASIS ANDROID DENGAN METODE CLASSIFICATION AND REGRESSION TREE - Krisnayana, I Dewa Made; Arya Mertasana, Putu; Sudarma, Made (Jurnal SPEKTRUM; Vol 7 No 3 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i03.p4, 2020)
Gastroenteritis is a disease that attacks the body's digestive system, especially in the small intestine and stomach through viruses and bacteria. In addition to its transmission caused virus and bacteria, it can also caused by unhygienic food and drink. However, people generally equate gastroenteritis with diarrheal disease, causing medical mismanagement that can be fatal. Therefore, this research trying to build an Android based application that can help people in diagnose gastroenteritis. So in this research, the application was build using Classification And Regression Tree using an Android platform and flutter extension. This research using historical data of 780 patients with 2 classes of disease, namely gastroenteritis and gastritis. The testing results is done to determine the peformance of application such as accuracy, precision , and recall of the application in diagnosing disease. According to confusion matrix testing results, the application that was build able to diagnose gastroenteritis and gastritis disease by obtaining an Accuracy of 85.1 %, Precision of 84 %, and Recall (application sensitivity in diagnosing) of 98 %.